(Pro)renin Receptor Activation Increases Profibrotic Markers and Fibroblast-like Phenotype Through MAPK-dependent ROS Formation In Mouse Renal Collecting Duct Cells - Gonzalez, Alexis A. (Clin Exp Pharmacol Physiol, 2017)
Recent studies suggested that activation of the PRR upregulates profibrotic markers through reactive oxygen species (ROS) formation; however, the exact mechanisms have not been investigated in CD cells. We hypothesized that activation of the PRR increases the expression of profibrotic markers through MAPK-dependent ROS formation in CD cells. Mouse renal CD cell line (M-1) was treated with recombinant prorenin plus ROS or MAPK inhibitors and PRR-shRNA to evaluate their effect on the expression of profibrotic markers. PRR immunostaining revealed plasma membrane and intracellular localization. Recombinant prorenin increases ROS formation (6.0 ± 0.5 vs. 3.9 ± 0.1 nM DCF/μg total protein, P<0.05) and expression of profibrotic markers CTGF (149 ± 12%, P<0.05), α-SMA (160 ± 20%, P<0.05), and PAI-I (153 ± 13%, P<0.05) at 10(-8) M. Recombinant prorenin induced phospho ERK 1/2 (p44 and p42) at 10(-8) and 10(-6) M after 20 min. Prorenin-dependent ROS formation and augmentation of profibrotic factors were blunted by ROS scavengers (trolox, p-coumaric acid, ascorbic acid), the MEK inhibitor PD98059 and PRR transfections with PRR-shRNA. No effects were observed in the presence of antioxidants alone. Prorenin-induced upregulation of collagen I and fibronectin was blunted by ROS scavenging or MEK inhibition independently. PRR-shRNA partially prevented this induction. After 24 h prorenin treatment M-1 cells undergo to epithelial mesenchymal transition phenotype, however MEK inhibitor PD98059 and PRR knockdown prevented this effect. These results suggest that PRR might have a significant role in tubular damage during conditions of high prorenin-renin secretion in the CD.